5-FLUOROURACIL IMPREGNATED NIOSOMAL-IN SITU GEL (THERMO-SENSITIVE) FOR ORAL CANCER: DESIGN, CHARACTERIZATION, IN VITRO/EX VIVO EVALUATION - SINGH, RAHUL KUMAR; DEORA, ANIRUDH SINGH (International Journal of Applied Pharmaceutics, 2022)
Objective: To formulate and characterize 5-fluorouracil loaded niosomal-in-situ gel for sustained drug delivery to reduce dosing frequency at the same time, follow a local drug delivery for cancer targeting. Methods: Cholesterol and span-60-based niosomes were prepared after following the modified ether injection method. Best formulation selected after characterization through FTIR, SEM, % Entrapment efficiency, zeta potential, polydispersity index, in vitro release, and vesicle size whereas, based on cold method niosomes encapsulated in-situ gel was formulated and characterized through gelling temperature and time, spreadability and syringe ability, gel strength, adhesive force, and drug release. Results: Based on various studies, included particle size, PDI, zeta potential value, % Entrapment efficiency and % drug release, F1 formulation was selected as a best formulation, as niosomal particle size of 388.3 nm proved a higher drug permeation through the buccal area, whereas PDI and zeta potential value of 0.304 and+50.5 are proved a uniform niosomal size with optimum charge distribution which helps to attain higher stability of the formulation, on the other hand % Entrapment efficiency of 87.825% proved that niosomes are capable to hold higher drug concentration; lastly 84.567% of drug release within 12 h of time period prove that higher amount of drug release occur by following sustained release pattern. On the other hand Mucoadhesion, gelling strength and in vitro permeation studies prove that niosomes containing in-situ gel has a capacity to adhere over the mucosa with minimum dissolution with saliva up to 12 h and is capable of 95% of drug permeation capacity. Lastly FTIR and SEM images confirmed about niosomal formation with optimum stability. Conclusion: 5-Fluorouracil encapsulated niosomal in-situ gel will be superior and effective alternative to parenteral dosage forms available in the market for mouth cancer treatment.